USING VIABLE SYSTEM MODEL TO ANALYSE INDONESIA’S ANTI-CORRUPTION STRATEGY - Nugroho Ari Setyawan (Asia Pacific Fraud Journal, 2018)
Indonesia’s fighting against corruption has a serious problem in relation to how to make all the institutions working together under a strong model. This paper uses the Viable System Model as a framework model for Indonesia’s anti-corruption measures. The model is used by author to understand the Indonesian anti-corruption parties’ measures in a single model, understanding the problems inherited to the agencies and giving solutions for them to improve anti-corruption measures for the effectiveness of the achievement of better Corruption Perception Index for Indonesia.